Rancang Bangun Aplikasi Penyedia Pekerjaan Lepas Trivial Menggunakan Metodologi Agile - Halim, Apriyanto; Antoline, William; Arbecco, Arbecco; Gunawan, Erin; Wijaya, Leonardi Rendy; Wijaya, Leonardo Randy (Jurnal Ilmiah Matrik, 2024)
Freelancers are individuals who perform specific tasks for a number of different organizations, rather than committing to a single one. By the mean of freelance marketplace technology, it is now easier for recruiters and freelancers to meet and discuss. However, jobs on most freelance marketplaces today are categorized, focusing on more highly-skilled jobs. Thus, jobs such as daily and trivial ones cannot be found. Therefore, this research aims to develop a freelance marketplace application to help solve the existing problem of freelance work supply demand. This application, by accommodating trivial freelance jobs, is expected to promote inclusivity by providing job opportunities for freelancers with general skill sets. This research is performed using agile methodology, consisting of requirement analysis, design, application development, and black box testing. It was obtained that the web application for admin and the mobile application for user are functioning properly and could met the users’ need.